Scaffolding to reduce misconceptions: A case study of solving a two-variable linear equation system problem based on students' cognitive styles - Pramesti, Laorentina Fitri Bella; Setyaningsih, Nining (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study aims to explain students' misconceptions in solving material problems of linear equations of two variables before and after scaffolding, the form of scaffolding given, and the effect of scaffolding. The research method used in this study is qualitative descriptive. This research was conducted at MTS Negeri Surakarta 1 with the subjects of 8th grade students who experienced misconceptions. The instrument used in this study is the Group Embedded Diagram Test to classify students based on their cognitive style. Students who experience misconceptions are given scaffolding level 2 (clarify, revise and restructure) and adapted to the needs of the students. Based on the research that has been done, students with a cognitive style of Field-dependent, as many as twelve students; intermediate field, as many as ten students; and depending on the field, as many as five students. Field-dependent students experience classification misconceptions in converting information into a system of two-variable linear equations and correlations in relating their knowledge to problem solving. Independent students experience classification misconceptions when determining the form of a system of linear equations in two variables. The result of this study is that the provision of scaffolding is an effective alternative in overcoming student misconceptions in solving the problem of a two-variable linear equation system.